Chemistry - Zumdahl, Steven S. (Boston, Mass : Houghton Mifflin, 1997)
Chemical foundations. Atoms, molecules, and ions. Stoichiometry. Types of chemical reactions and solution stoichiometry. Gases. Thermochemistry. Atomic structure and periodicity....
Keywords: Chemistry; Chemistry